Transmitting and receiving equipment for radiocommunication. Radio-over-fibre technologies for electromagnetic-field measurement. Antenna near-field pattern measurement using optical techniques in terahertz-wave bands Part 3, (9th September 2022) - British Standards Institution,
No abstract available